Potensi Antioksidan Kedelai (Glycine Max L) Terhadap Penangkapan Radikal Bebas - Andestya Nanda Pratama; Hendri Busman (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Free radicals are molecules that have unstable and reactive properties, because they have one or more unpaired electrons. Free radicals can attack vulnerable compounds such as lipids and proteins, which will eventually cause dangerous diseases. Free radicals threaten the health of the body because of their reactive and unstable nature, because of their instability, free radicals react with molecules that are closest after entering the body, and produce other free radicals, and eventually become a chain reaction that can threaten the health of the body. Soybean (Glycine max L) has antioxidant compounds that can react with free radicals and stop the rate of free radicals to react with molecules in the body, namely isoflavones and other compounds, such as proteins, fats, and vitain A, C and D. Soybean (Glycine max L) has been shown to play an important role in healing or inhibiting diseases caused by free radicals, as well as the antioxidants contained, namely isoflavones that are consumed regularly can protect the body from free radicals